EKSISTENSI DAN MAKNA SIMBOLIK TRADISI KELAHIRAN JAWA: STUDI FENOMENOLOGI TERHADAP PENGALAMAN RITUAL BROKOHAN, SEPASAR, DAN SELAPANAN, SUKOSEWU, BOJONEGORO - Anita, Wiwik; Iqbal Birsyada, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research seeks to uncover why the Brokohan, Sepasaran, and Selap-anan traditions persist despite the modern digital age. This cultural preservation phenomenon is particularly intriguing because rural areas like Kedal Hamlet in Bo-jonegoro continue to experience significant social transformations. It turns out that these Javanese birth ritual series are not merely outdated customs that remain unchanged, but serve as genuine ways for communities to express sincere re-spect for each stage of the beginning of human life. Using a phenomenological approach, this research explores the feelings and experiences of community members, from the parents of newborns to senior village elders, to understand what they actually feel, undergo, and think during the ritual process. Research da-ta was collected directly from the field through observation and in-depth interviews to capture the essence of each stage. The results are quite surprising; the exist-ence of these traditions is still well-maintained through collective awareness to preserve the balance between humans, nature, and ancestors. The meanings be-hind the offerings, such as the jenang abang putih (red and white glutinous rice dish) and the special placenta care, prove to be profound symbols regarding hu-man origins and the balance of the Javanese world or cosmology. Psychologically, these transition rituals have been found to provide inner peace, a sense of securi-ty, and strengthen their identity as culturally Javanese people. Ultimately, Broko-han, Sepasaran, and Selapanan are not merely safety ceremonies for newborns, but also serve as social venues for community mutual support through coopera-tion. Additionally, these traditions represent a unique way to preserve local values while welcoming new life into the world.Keywords: holistic strategy, best prac-tice,qualitative case study, pencak silat, pancasila student profile. KEYWORD : Symbolic Meaning, Phenomenology, Javanese Tradition